The Effect Of Training And Career Development On Employee Performance PT. Indofood Bengkulu City - Subandrio; Andika M Saputra (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2024)
This study aims to determine the influence of training and career development on the performance of PT employees. Indofood Bengkulu City. This type of research uses quantitative descriptive research methods. The population used in this study was employees of PT. Indofood Bengkulu City. The number of respondents in the study amounted to 55 people. The method of data collection is using questionnaires and using analysis techniques using multiple linear regression analysis test and hypothesis test i.e. test t and f test. Based on the results of multiple linear regression, the form of regression equation Y= 2.441 + 0.479 X1 + 0.351 X2 and the results of t test and f test this study can be concluded that Training has a positive and significant effect on Employee Performance, this is evidenced by the results of t test showing the value of thitung > ttable (3.392 > 1.674) and (sig α = 0.002 < 0.005). This means that H_0 is rejected and H_a is accepted. Career Development has a positive and significant effect on Employee Performance, this is evidenced by t test results showing thitung values > ttable (3.197 > 1.674) and (sig α = 0.001 < 0.005). This means that H_0 is rejected and H_a is accepted. Training (X1) and Career Development (X2) together have a significant effect on the Performance of Employees (Y) at PT. Indofood City Bengkulu, this is proved by the F test showing a count value > ftable, i.e. 21,277 > 3.17 and (sig α = 0.000 < 0.005). This means that H_0 is rejected and H_a is accepted.